HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG ANTENATAL CARE DENGAN KESESUAIAN KUNJUNGAN ANTENATAL CARE DI PUSKESMAS PINTU PADANG KECAMATAN BATANG ANGKOLA - Parinduri, julidia safitri; Tresia, Anita . (Universitas Aufa Royhan, 2016)
ANC is a pregnant mother's visit to the midwife or doctor as early as possible since she felt herself to be pregnant to get service / antenatal care. This research method is correlation. The population in this study were all pregnant mothers Post as many as 32 people, with a sample size of 32 respondents, taken tottal sampling. Data was collected through interviews using a questionnaire and then presented in a frequency distribution table and cross table. The results of this study showed p = 0.003 (p <0.05) means that there is a significant correlation between the respondents' knowledge with the suitability of antenatal care visits and obtained p = 0.004 (p <0.05) means that there is a significant relationship between the attitude of the respondents to the suitability of the visit antenatal care. It is suggested to pregnant women at health centers Pintu Padang in order to come regularly to the nearest health center or CPM checkups at least 4 times during pregnancy